The Influence of Entrepreneurial Knowledge, Family Roles, and Social Media on Interest in Entrepreneurship with Self Efficacy as Mediator Variable - Wahyuni, Kristin; Yanto, Heri; Oktarina, Nina (Universitas Negeri Semarang, 2021)
Creation of spirit of entrepreneurship that is high on students' vocational beginning of their interest in entrepreneurship was itself so that should be fostered to develop the students of SMK. The emergence of interest in entrepreneurship does not appear so alone, but some factors influence it. The purpose of this study was to determine the role of entrepreneurial knowledge, the role of family, social media, and self-efficacy in increasing interest in entrepreneurship. This research uses a quantitative approach. The research population was 205 students of class XI of the Online Business and Marketing Expertise Program at State Vocational Schools throughout Jepara Regency with a sample of 136 respondents. Methods of data collection using a questionnaire. Analysis of data using analysis descriptive and analytical path. Results of the study showed that knowledge of entrepreneurship affects self-efficacy. Social media affects self-efficacy. The role of family influence on the knowledge of entrepreneurship. The role of the family does not affect self-efficacy. Self-efficacy affects an interest in entrepreneurship. Entrepreneurial knowledge affects an interest in entrepreneurship. Social media does not affect entrepreneurial interest. The role of the family has an impact on social media. Social media affects entrepreneurial knowledge